On the Testability of the Equivalence Principle as a Gauge Principle Detecting the Gravitational t3 Phase - Marletto, Chiara; Vedral, Vlatko (Frontiers in Physics, 2020)
There have been various claims that the Equivalence Principle, as originally formulated by Einstein, presents several difficulties when extended to the quantum domain, even in the regime of weak gravity. Here we point out that by following the same approach as used for other classical principles, e.g. the principle of conservation of energy, one can, for weak fields, obtain a straightforward quantum formulation of the principle. We draw attention to a recently performed test that confirms the equivalence principle in this form and discuss its implications.